1982
DOI: 10.1002/j.1875-9114.1982.tb03210.x
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil Hydrochloride: Pharmacological Properties and Role in Cardiovascular Therapeutics

Abstract: Verapamil hydrochloride, a prototype calcium antagonist, is now marketed in the United States for the acute treatment of supraventricular tachyarrhythmias and for chronic management of vasospastic and chronic stable angina. It inhibits the slow inward channel in in the heart and blocks calcium influx in smooth muscle. Its intrinsic negative inotropic action, which is apparent in isolated tissues, is offset in vivo by peripheral vasodilation. It has a mild, noncompetitive sympathetic antagonist effect; its most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 155 publications
0
8
0
1
Order By: Relevance
“…It reduces the cellular influx of Ca 2+ [20] and thus has an indirect effect on the Ca 2+ activated potassium channel. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It reduces the cellular influx of Ca 2+ [20] and thus has an indirect effect on the Ca 2+ activated potassium channel. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Antagonism by verapamil of respiratory depression and tachycardia produced by morphine was unrelated to morphine levels in plasma. Thus, the explanation of verapamil-morphine interactions on respiration and cardiovascular function is not pharmacokinetic.Calcium channel antagonists, such as verapamil and diltiam, are used clinically in cardiovascular therapy (Henry 1980;Baky & Singh 1982; Wagniart et a1 1982). Studies of opioid analgesia, tolerance and dependence in rats have used drugs that inhibit calcium binding and transport.…”
mentioning
confidence: 99%
“…Calcium channel antagonists, such as verapamil and diltiam, are used clinically in cardiovascular therapy (Henry 1980;Baky & Singh 1982; Wagniart et a1 1982). Studies of opioid analgesia, tolerance and dependence in rats have used drugs that inhibit calcium binding and transport.…”
mentioning
confidence: 99%
“…The combination of Pgp inhibitor verapamil with GSK923295 induced the G2/M arrest in MESSA Dx5 cells followed by apoptosis, which restored the cytostatic effect of GSK923295. Initially, verapamil was developed as a calcium channel blocker [30,31]. Subsequently, it has been reported that verapamil is a chemosensitizing compound which diminishes multidrug resistance and increases the intracellular drug accumulation by competitive inhibition of drug transport through P-glycoprotein [32].…”
Section: Discussionmentioning
confidence: 99%